Bacterial blight of peas: phytosanitary risks and disease diagnostics - Trepach, A.O.; Krupenik, M.F. (Quarantine and plant protection, 2026)
Goal. To analyze and summarize information from literary sources on the spread of Pseudomonas syringae pv. pisi — the causative agent of bacterial blight of peas, symptoms of the disease, risks of spread and methods of phytosanitary diagnostics of the pathogen. Methods. Analysis, synthesis, generalization. Results. The significance of P. syringae pv. pisi as a harmful organism leading to crop losses in field peas and some other legumes has been substantiated. This pathogen is widely distributed in many regions of the world, including Ukraine, as a result of which it was excluded from the list of regulated pests of the European and Mediterranean Plant Protection Organization and is currently regulated only in a few countries around the world. Since P. syringae pv. pisi is capable of spreading with asymptomatic infected plant material, in particular grain, this creates phytosanitary risks, especially relevant given Ukraine’s trade and economic ties with countries where this pathogen is regulated. Therefore, for the unhindered export of agricultural products, there is a need for phytosanitary monitoring of pea crops for the presence of P. syringae pv. pisi. However, no interregional diagnostic protocol PM has been developed for this organism. However, there are enough scientific publications that highlight the diverse studies of these bacteria, as well as the validated methods for their detection in pea seeds. Conclusions. P. syringae pv. pisi are phytopathogenic bacteria that are constantly in the spotlight in countries where peas are major crops. In Ukraine, the relevance of phytosanitary monitoring of pea crops for bacterial blight caused by the specified pathogen is significantly increasing today, against the backdrop of expanding trade cooperation with China. This requires up-to-date information on the development of the disease for conducting crop inspections and significant attention to the choice of pathogen detection methods during phytosanitary examination.